Web conferencing for distance learning - Nguyễn Nhứt Lam (Griffith College Dublin, 2023)
Nowadays, with the evolution of the Internet and web techno logies, web conferencing systems has played an important role in distance education. The fundamental features that every web conferencing system has are the real -time communications capabilities between web browsers. However, it is the fact that some of them still require web browser-specific implementations or proprietary plugins. WebRTC, a new technology, turned out to be a suitable solution. This technology enables real-time communication capability between web browsers without relying on other third-party plugins. The Thesis comes from the above ideas. It is about designing and implementing a web conferencing system using WebRTC technology .